1987
DOI: 10.1002/chin.198708208
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Tetrazoles. Part 21. Reaction of Benzonitrile with Azides.

Abstract: 208 ChemInform Abstract Benzonitrile (I) reacts with ammonium, alkyl-, dialkyl-, and trialkyl ammonium azides (II) to give 5-phenyltetrazole (III). Tetraalkylammonium azides do not react under these conditions. (IR-, NMR-data).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[109] This is most likely the reason why these reactions proceeded with high regioselectivity, even in the case of unsubstituted tetrazole. [111] However, the reaction between a 5-ST with a more compact substituent at the 5-position yielded the two isomers 34 and 35 in comparable amounts, putting the major role of the above hypothesis into question. However, the influence of these associates on the reaction rates or regioselectivity is not still clearly understood, although many examples have shown that the regioselectivity is controlled in the same manner as in the case of the tetrazolate anion.…”
Section: Alkylation Of 5-stsmentioning
confidence: 99%
“…[109] This is most likely the reason why these reactions proceeded with high regioselectivity, even in the case of unsubstituted tetrazole. [111] However, the reaction between a 5-ST with a more compact substituent at the 5-position yielded the two isomers 34 and 35 in comparable amounts, putting the major role of the above hypothesis into question. However, the influence of these associates on the reaction rates or regioselectivity is not still clearly understood, although many examples have shown that the regioselectivity is controlled in the same manner as in the case of the tetrazolate anion.…”
Section: Alkylation Of 5-stsmentioning
confidence: 99%
“…Since the corresponding nitrile ( 1 ) was commercially available, it was proposed that the tetrazole ring should be introduced directly via azide cycloaddition. We were thus faced with the task of deciding which of the dozens of tetrazole-forming reaction conditions to employ. Considering ease of operation, reagent cost, and waste minimization, we decided to first investigate the simple conditions reported by Finnegan, Henry, and Lofquist in 1958: NaN 3 in the presence of NH 4 Cl in DMF . While nitrile 1 was successfully transformed to 2 under these conditions, the reaction was unfortunately very sluggish, as is often the case for ortho-substituted nitriles. ,,, Full consumption of the nitrile starting material required >40 h at 120 °C with a significant excess of reagents (2.0 eq NaN 3 , 2.5 eq NH 4 Cl).…”
Section: Resultsmentioning
confidence: 99%
“…In order to avoid the use of hydrazoic acid, dozens of alternative protocols have since been developed for the conversion of an aryl nitrile to the corresponding 5-aryltetrazole . In the simplest of these procedures, hydrazoic acid is generated in situ by the reaction of sodium azide with a weak Brönsted acid, typically ammonium chloride or triethylamine hydrochloride (Scheme , eq B) . Alternatively, myriad Lewis acids have been demonstrated to mediate the reaction between an aryl nitrile and sodium azide.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these salts increase the reactivity of the azide ion. They are prepared using ammonium chloride, 22,23 alkylamine hydrochlorides, 14,15 tetramethylguanidinium chloride, 24 boron trifluoride etherate 25 and aluminium chloride. 21 Temporary protection of the double bond of acrylonitrile by addition of dimethylamine has made it possible to avoid polymerisation and resinification in the reaction of the azide ion with the nitrile group of 3-dimethylaminopropionitrile: 5-(2-dimethylaminoethyl)tetrazole (3) was prepared in high yield.…”
Section: Synthesis Of C-vinyltetrazolesmentioning
confidence: 99%